Carbapenem susceptibility breakpoints, clinical implications with the moving target. Issue 4 (2nd April 2016) - O'Donnell, J. Nicholas; Miglis, Cristina M.; Lee, Jane Y.; Tuvell, Merika; Lertharakul, Tina; Scheetz, Marc H.
ABSTRACT: Carbapenems are primary agents used to treat a variety of Gram-negative multi-drug resistant infections. In parallel with increasing use, increasing resistance to carbapenem agents has manifested as increased minimum inhibitory concentrations (MICs). To attempt to improve clinical outcomes with carbapenems, the Clinical Laboratory Standards Institute and the Food Drug Administration decreased susceptibility breakpoints. The European equivalent expert committee, the European Committee on Antimicrobial Susceptibility Testing, also utilizes lower MIC susceptibility breakpoints. This review focuses on the rationale for recent breakpoint changes and the associated clinical outcomes for patients treated with carbapenems for infections with varying MICs proximal to the breakpoint. Supporting pharmacokinetics and pharmacodynamics that underpin the breakpoints are also reviewed.